Drug availability: considerations for the hospital pharmacist. Issue 2 (12th March 2012) - Mica, A.; Green, L.
Abstract : Background: Hospital pharmacists play a key role in formulary decision-making. As a part of that role, it has become important to consider the assurance of drug supply for their institutions, as adequate drug availability is a growing global concern. With drug shortages, both physicians and pharmacists need to consider less desirable options including rationing drugs, delaying critical treatments, and utilising less efficacious medications. Regulatory agencies are striving to develop processes to address drug shortages, including rapid notifications. While this may aid healthcare providers in managing shortages, it does not address their ability to maintain continuous supply. Pharmaceutical and biotechnology manufacturers face operational efficiency challenges, placing stable supply to patients at risk. Purpose: Utilising biologics as an example, this report highlights critical supply chain parameters that pharmacists should consider when evaluating a manufacturer's ability to maintain and deliver a continuous supply of medications. Materials and methods: Through examples, key considerations for ensuring drug availability in the complex environment of manufacturing and distribution challenges are outlined. Results: Key factors that can enable biologic manufacturers to ensure continuous supply of high quality products to patients include: 1) integration of global manufacturing and distribution information systems that link patient demand to production scheduling; 2) qualification of suppliers and dual sourcing of raw materials; 3) redundant manufacturing capabilities and strategic capacity management; 4) maintenance of strategic safety stocks to minimise impact of manufacturing delays/interruptions; and 5) active management of robust and secure cold chain distribution networks. These factors require leveraging resources, both financial and human, to ensure that approved drugs are available through normal operations, and during periods of supply shortages. Conclusions: In conclusion, it should become an integral part of the hospital pharmacist's role to understand and take into consideration how a manufacturer manages drug supply when weighing formulary decisions.